Study guide with student's solutions manual for Statistics for management and economics - Keller, Gerald; Warrack, Brian (Pacific Grove, CA : Duxbury Press, 1998)
What is statics? Graphical descriptive techniques. Art and science of graphical presentations. Numerical descriptive techniques. data collection and sampling. Probability and discrete probability distributions. Continuous probability distribution...
Keywords: Economics; Management; Statistical methods; Economics -- Statistical methods; Management -- Statistical methods